ANALISIS PENGARUH PERKEMBANGAN PASAR MODERN TERHADAP KEBERLANGSUNGAN PASAR TRADISIONAL TENTE WOBA KAB. BIMA - Syahrul dan Sri Ernawati (JOURNAL SCIENTIFIC OF MANDALIKA (JSM), 2021)
Currently, the development of the shipping service industry has increased quite rapidly. The era of globalization requires humans to have high mobility. One service industry that is also experiencing dynamics in its development is goods delivery services. In the tight competition in the shipping service business, entrepreneurs are required to make breakthroughs to achieve customer satisfaction, including by providing improved service quality, providing various facilities, and setting prices that are appropriate to achieve consumer satisfaction. This study aims to determine the analysis of customer satisfaction at the j & t service company. This research uses a quantitative approach with a survey method, while this type of research is a descriptive study. The population in this study are consumers who have used the services of j & t, the number of samples taken in this study were 96 respondents. The research instrument used a questionnaire with a Likert scale. The data analysis used is validity test, reliability test, statistical analysis test (One-Sample Statistics, One-Sample Test). To test the effect between variables using SPSS (Statistical Service Product Solutions) version 23.00. Based on the results of the one-sample t-test on J&T Kota Bima it is said to be not good because it is less than 70%, which means that customer satisfaction on J&T services is not in accordance with consumer desires.